(untitled) (Global Journal of Management and Business Research, 2023)
The research analyzes into PRC s strategic intensions behind the militarization of the South China Sea It is hypothesized that the geopolitical and realpolitik statures in the South China Sea is signatory to a new Space Race The analysis obtained positive results to the hypothesis and type I and type II errors are discussed The research holds the possible type I error as inevitable and its implications relevant to the mapping of problem solutions The supply advantage in the natural gas hydrate market is cognized to be the strategic leverage in the totalitarian and dictatorial power frameworks in the global institutions